PENGEMBANGAN MODEL AGROINDUSTRI DESA GONDANGAN KECAMATAN JOGONALAN KABUPATEN KLATEN - Didik Indarwanta; Ida Susi Dewanti; Eny Endah Pujiastuti (Universitas Muhammadiyah Semarang, 2015)
This research is a continuation of of previous studies that have identifying related institutions which support the development of Gondangan as an agroindustriesvillage.Furthermore,the model that had been developedwas applied in order to support the development of the agro-industry. Further research is done by implementing model of the SME snacks at Gondangan village, Klaten.Applications undertaken include training, mentoring, study visits and so on. In general, this study successfully demonstrated that main actors and supporting actors who are in the model are interrelated and mutually supportive even though the role of each actor is not maximized. To maximize the role of each actors need assistance and rebuild new model to develop Gondangan as an agroindustries village.Keywords: Model, Development, Agro-Industry, SMEs